Improving 9th graders’ oral production in english through cooperative learning strategies (2020)
The aim of this paper is to develop a pedagogical proposal that shows the importance and the role that cooperative methodology plays in the development of speaking skills. It also was implemented in the classroom in order to develop a better understanding and acquisition of the second language. Speaking tends to be considered the most difficult skill to be developed, especially for us, Spanish speakers, since it is quite difficult to practice speaking when the student does not live in an English speaking country. For this reason, we developed and implemented 3 units that involve cooperation and communicative strategies from a sociocultural perspective with the aim of enhancing students' oral production through the use of authentic materials.